Analysis of Class VIII Students' Critical Thinking Ability in Solving Numeration-Based Questions at SMPN 2 Kunto Darussalam - Muzayanah, Fitri Isnani; Afri, Lusi Eka; Nurrwahmawati, Nurrahmawati (Science, Technology and Education Care (STEDCA), 2025)
This study aimed to describe the critical thinking skills of grade VIII students in solving numeracy-based problems at SMP Negeri 2 Kunto Darussalam. This research used a qualitative approach with a descriptive type. The subjects in this study were class VIII students of SMP Negeri 2 Kunto Darussalam, comprising 25 students. Then, six students, consisting of two students with high scores, two students with medium scores, and two students with low scores, were selected as interview subjects. Data validity was measured using triangulation techniques. The data analysis technique used the Miles and Hubberman (1984) model, which consisted of data reduction, data presentation, and concluding. The results showed that the critical thinking ability of grade VIII students in solving numeracy-based problems at SMP Negeri 2 Kunto Darussalam was moderate, with an average score of 57.8. When viewed from the FRISCO stages, focus was classified as a high category with a value of 2.76, reason was classified as a high category with a value of 2.72, inference was classified as a medium category with a value of 1.2, situation was classified as a medium category with a value of 1.16, clarity was classified as a medium category with a value of 1.52, and overview was classified as a medium category with a value of 1.6.